2016
DOI: 10.3941/jrcr.v10i9.2885
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Isometric Contraction of Anterior Cervical Muscles on Cervical Lordosis

Abstract: This study shows no evidence that hypertonicity, as seen in muscle spasms, of the muscles responsible for anterior head translation and anterior head flexion have a significant impact on cervical lordosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…However, we found no statistically significant differences in the control group’s cervical lordosis who were subjected to neck stretches and IR; which should also reduce muscle spasm/tightness. The lack of a cause-and-effect association between muscle spasm and hypo-lordosis in our study is consistent with a study of acute and chronic neck pain patients by Helliwell et al [ 35 ] and with the biomechanical investigation performed by Fedorchuk et al [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, we found no statistically significant differences in the control group’s cervical lordosis who were subjected to neck stretches and IR; which should also reduce muscle spasm/tightness. The lack of a cause-and-effect association between muscle spasm and hypo-lordosis in our study is consistent with a study of acute and chronic neck pain patients by Helliwell et al [ 35 ] and with the biomechanical investigation performed by Fedorchuk et al [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, for the cervical spine it was demonstrated that cervical spine alignment alterations (i.e. kyphosis) are not resulting from muscle spasms 39 ) ; in fact, muscle activity mostly increases the lordosis, not straightening it as traditionally assumed. For this reason, traditional treatments (not LET) aimed at the back muscles such as stretching, hot packs and interferential therapy may lessen pain, lessen disability and increase flexibility (albeit temporarily) but not affect the structural spine alignment.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the Moustafa trials [49][50][51][52][53] were so designed to include physiotherapeutic methods that would relieve any muscle spasms, but comparison treated patients, not receiving CET, still did not achieve any improvements in lordosis. Also, Fedorchuk et al recently showed that cervical muscle engagement simulating muscle spasm most likely induces an increase in curvature, not a straightening of the cervical spine 76) .…”
Section: Discussionmentioning
confidence: 99%